The Advantages of Indocyanine Green Fluorescence Imaging in Detecting and Treating Pediatric Hepatoblastoma: A Preliminary Experience - Cho, Yu Jeong; Namgoong, Jung-Man; Kwon, Hyun Hee; Kwon, Yong Jae; Kim, Dae Yeon; Kim, Seong Chul (Frontiers in Pediatrics, 2021)
Background: Currently, indocyanine green (ICG) fluorescence imaging enables radical surgical resection in hepatoblastoma (HB) and has beneficial uses; however, its usage in pediatric patients is still limited. Methods: From 2015 to 2019, 17 hepatoblastoma patients underwent 22 fluorescence-guided surgery using ICG. ICG (0.3 mg/kg) was intravenously injected 24–48 h before the operation. With ICG/NIR camera, intraoperative identification of biological structures and demarcation of mass were conducted. Results: ICG fluorescence-guided surgery was performed for hepatoblastoma in 22 cases: 16, 1, and 2 cases underwent anatomic resection, partial hepatectomy, and liver transplantation, respectively. Six patients accompanied lung metastasis at the time of surgery, and two patients underwent lung surgery using ICG. The median interval from ICG injection to surgery was 38.3 hours (range, 20.5–50.3 hours). The median tumor size was 36.5 mm (range, 2–132 mm). According to the pathologic finding, the median safety margin was secured for 6 mm (range, 0–11 mm) and there was no residual finding at the liver at the follow-up computed tomography (CT). Conclusions: ICG fluorescence imaging in children with HB was feasible and safe for tumor demarcation and enhancing the accuracy of radical tumor resection.